2019
DOI: 10.4037/ccn2019238
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Analysis of a Free Water Protocol in Acute Trauma and Stroke Patients

Abstract: Background Free water protocols allow patients who aspirate thin liquids and meet eligibility criteria to have access to water or ice according to specific guidelines. Limited research is available concerning free water protocols in acute care settings. Objectives To compare rates of positive clinical outcomes and negative clinical indicators of a free water protocol in the acute care setting and to continue monitoring participants discharged into the hospital system's rehabilitation setting. Positive clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
1
0
2
Order By: Relevance
“…A free water protocol in the presence of aspiration may be recommended for swallow maintenance and QOL. Recent studies have demonstrated an absence of negative clinical indicators associated with this approach [ 13 ].…”
Section: Slp Management Of Dysphagiamentioning
confidence: 99%
“…A free water protocol in the presence of aspiration may be recommended for swallow maintenance and QOL. Recent studies have demonstrated an absence of negative clinical indicators associated with this approach [ 13 ].…”
Section: Slp Management Of Dysphagiamentioning
confidence: 99%
“…In den folgenden Jahren wurden einige, größtenteils kontrollierte Studien zum FWP durchgeführt (n = 8). Untersucht wurden unterschiedliche Patientenpopulationen, unter anderem Patienten nach Schlaganfall [8,9,10], Schädel-Hirn-Trauma [11,12] oder auch tracheotomierte und beatmete Patienten mit Critical-Illness-Polyneuropathie [13]. Die Schwere der neurologischen Störungen variierte, das FWP wurde sowohl bei leichter betroffenen Patienten [14] als auch bei Personen mit hohem Supervi-sionsbedarf bei der Umsetzung des Protokolls untersucht [11,15].…”
Section: Studienlageunclassified
“…Auch die weiteren Studien zum FWP weisen Limitationen auf. Häufig wurden nur kleine Fallzahlen untersucht (beispielsweise 16 Patienten bei Pooyania et al [14]; eine Ausnahme ist die Untersuchung von Kenedi et al [12] mit je 52 Patienten in Studien-und Kontrollgruppe). Die Beobachtungszeiträume waren teilweise sehr kurz (beispielsweise 8 Tage bei Karagiannis et al [15]).…”
Section: Diskussionunclassified
“…The FWP specifies certain guidelines including regular oral care, which are designed to minimize risk of adverse consequences (Panther, 2005). Several randomized control trials (RCTs) have been conducted, the majority in the context of inpatient rehabilitation (Carlaw et al., 2012; Garon et al., 1997; Karagiannis et al., 2011; Karagiannis & Karagiannis, 2014; Murray et al., 2016), with only two in the acute care setting (Bernard et al., 2015; Kenedi et al., 2019). Two subsequent meta‐analyses concluded that FWPs do not increase the risk of developing lung complications and result in a numerical increase in fluid intake and improved quality of life for adults in inpatient rehabilitation with a low risk of pneumonia when compared with thickened fluids or nil by mouth (Kaneoka et al., 2017; Gillman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%